PENGARUH EDUKASI KESEHATAN DENGAN MEDIA LEAFLET TERHADAP TINGKAT PENGETAHUAN PADA IBU DALAM MENGHADAPI MENOUPOUSE - Italia; Fera (LPPM STIKes Mitra Adiguna, 2026)
Menopause is a natural stage in a woman's reproductive life, marking the transition from the reproductive to the non-reproductive period due to a decline in estrogen and progesterone hormone levels. The World Health Organization (WHO) estimates that by 2030, approximately 1.2 billion women worldwide will be aged 50 years and older. Insufficient knowledge about menopause may hinder premenopausal women from adequately preparing for and adapting to this stage of life. This study aimed to determine the effect of health education using leaflets on women's knowledge of menopause in 2024.This study employed a quantitative pre-experimental design using a one-group pretest–posttest approach. The study population consisted of premenopausal women who attended the Kenten Community Health Center in Palembang in November 2024. A purposive sampling technique was used to recruit 30 respondents. Data were analyzed to compare participants' knowledge before and after the health education intervention. The results showed a statistically significant increase in respondents' knowledge following the intervention (p < 0.001), indicating that health education delivered through leaflets effectively improved women's knowledge about menopause. It is recommended that healthcare providers at the Kenten Community Health Center continue implementing leaflet-based health education as an educational strategy to enhance women's understanding of menopause and improve the quality of health promotion services.